Is the crucible reproducible? Reconciling melting experiments with thermodynamic calculations - White, R.; Stevens, G.; Johnson, Tim (Mineralogical Society of Canada, 2011)
Experimental studies and thermodynamic modelling have advanced our understanding of partial melting in the crust and have provided a frame-work for the interpretation of migmatites, residual granulites and granites. Each approach has advantages and pitfalls, and each is more appropriate than the other for investigating particular aspects of the melting process. A comparison of these two approaches may be useful because, together, they potentially give more information. A comparison of a small number of experiments with model calculations using equivalent bulk compositions shows important consistencies between the results, especially regarding the overall topologies of key melting equilibria. Despite this, several significant differences between the two approaches remain, though the sources of these differences are difficult to determine.